Lung abscesses. Fatal evolution due to sepsis. - Puig, Roberto; Goja, Beatriz; Delbene, Roberto; Pérez Penco, Ernesto; Martínez, José L (Cirugía del Uruguay, 1989)
Authors present three cases of lung abscesses and conclusions from an up to date revision on the subject.